(untitled) (Journal of Life and Earth Science, 2014)
Bangladesh is a land scarce country where per capita cultivated land is only 12.5 decimals. It is claimed that every year about one percent of farm land in the country is being converted to non-agricultural uses. The study is based mainly on field survey covering 2 villages (Narikel Baria and Baze Silinda) from 10 sub-urban villages around Rajshahi City Corporation under Paba Upazila of Rajshahi district. The study area was selected purposively and the respondents of this research work were selected randomly. The major focus was on to mention the general land use pattern of the area, estimates the agricultural land conversion besides determining the causes and consequences affecting such conversion. Both Narikel Baria and Baze Silinda villages were selected as study area because of its relatively higher growth in infrastructure. In order to fulfill the goal of this study, primary and secondary data were collected from various sources and to analyze and process of collected data the SPSS, Excel and Arc GIS software were used. Different types of descriptive statistics were applied for representing the analyzed data. It is observed that the land conversion form agriculture to non-agriculture allied in recent time is more than the previous time due to gradually increasing land demand in housing and relevant services which invites adverse impact on agricultural land as well as its dependent population. So, it is necessary to take integrated land-use planning to offer better options for the fulfillment of land demand both of housing and agricultural sectors. DOI: http://dx.doi.org/10.3329/jles.v8i0.20136 J. Life Earth Sci., Vol. 8: 21-30, 2013